Komuniciranje izbranih primerov suš na Slovenskem v 20. stoletju - Osojnik, Janez; Friš, Darko; Matjašič Friš, Mateja; Hazemali, David (Komuniciranje okoljske krize, 2025)
This paper aims to present, through selected examples, the level of attention Slovenian newspapers devoted to the phenomenon of droughts in the Slovenian Lands during the 20th century, and, consequently, how the communication of these events evolved over time. The study focuses on drought events that occurred in 1921, 1939, 1950, 1952, 1962, and 1983, a period when most of the Slovenian ethnic territory was part of the Yugoslav state. Particular attention is given to the ways drought conditions and high air temperatures were described, as well as to the consequences of these natural disasters for human life that were emphasized. The findings are linked to theoretical principles concerning the communication of natural disasters and extreme events. The analysis is placed within the context of environmental history; therefore, a brief historical overview of the occurrence and frequency of droughts worldwide, their impacts on humanity, and the communication of natural disasters is provided at the beginning.